2022
DOI: 10.1371/journal.pone.0270527
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aging on the fracture resistance of different types of screw-cement-retained implant-supported zirconia-based restorations

Abstract: Structural durability of screw-cement-retained implant-supported zirconia-based restorations is an important factor in choosing the best type of restoration for clinical use. This study aimed to evaluate the effects of thermocycling on the fracture resistance of different types of screw-cement-retained implant-supported zirconia-based restoration. Two experimental groups (monolithic zirconia and porcelain-veneered zirconia) and a control group of porcelain-fused-to-metal restorations were fabricated via CAD-CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…4 Second, its effect on occlusion, the screw retained prostheses have some drawbacks, such as the necessity for optimal implant location. 11,12 Furthermore, the holding screw appears to be more susceptible to lateral bending, tipping, and elongation stresses, which could lead to screw loosening or screw fracture. Cement-retained restorations can be employed to minimize such drawbacks while also broadening the material spectrum to incorporate more restorative materials, such as all-ceramic materials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Second, its effect on occlusion, the screw retained prostheses have some drawbacks, such as the necessity for optimal implant location. 11,12 Furthermore, the holding screw appears to be more susceptible to lateral bending, tipping, and elongation stresses, which could lead to screw loosening or screw fracture. Cement-retained restorations can be employed to minimize such drawbacks while also broadening the material spectrum to incorporate more restorative materials, such as all-ceramic materials.…”
Section: Discussionmentioning
confidence: 99%
“…Fracture of veneering porcelain occurs frequently. 11 Zhang et al, revealed that the material and geometric features of MZ ceramics, as well as the elimination of the interface between layered materials and zirconia frameworks, could potentially enhance restoration performance. 15 The digital cutback in the monolithic zirconia allows for some translucency in the restorations.…”
Section: Discussionmentioning
confidence: 99%
“…21 Furthermore, some studies have shown that thermocycling or mechanical aging of the crowns will decrease the fracture resistance of the crowns and could accelerate the damage of ceramic materials. 22,23 In this study, all specimens were thermo-cycled for 1000 cycles between 5 and 55 c before testing, a clinical condition that has been adopted by many studies. 14,24 Around 70% of the crystalline phase in LDGC is incorporated into the glassy matrix.…”
Section: Discussionmentioning
confidence: 99%
“…All the access holes were filled with polytetrafluoroethylene film (Teflon tape) up to 2 mm apical to the occlusal plane as measured with a periodontal probe. After that, a bulk of composite resin (Esthet-X HD; Dentsply Sirona, USA) was placed, shaped, and light-cured for 40 seconds on the orifice to fill the screw access hole to the level of the occlusal plan ( Fig 3 ) [ 32 ]. The procedures were all performed by a single skilled dental technician.…”
Section: Methodsmentioning
confidence: 99%
“…Perpendicular compressive force to the central fossa of crowns was chosen for the fracture test as it simulated the most common force clinically applied to these teeth [ 34 ]. A compressive load was applied at a crosshead speed of 0.5 mm/min by a Universal Testing Machine (Shimadzu Autograph AG-50kNE, Shimadzu Co., Ltd, Japan) [ 32 ] ( Fig 4 ).…”
Section: Methodsmentioning
confidence: 99%